Role of Neutrophil-Lymphocyte Ratio (NLR) in predicting development of organ failure in Acute Pancreatitis - Saqeb, Khan Md Nazmus; Raza, Abu Khalid Muhammad Maruf (Mediscope, 2021)
Background: Different modalities are available for predicting development of organ failure in Acute Pancreatitis. A single marker with high sensitivity and specificity is yet to be identified. This study intends to find out the utility of Neutrophil Lymphocyte Ratio (NLR) in predicting development of organ failure in Acute Pancreatitis. Methods: A total of 117 patients admitted with acute pancreatitis were included. Clinical parameters and biochemical tests were recorded on admission and on day 3 & day 5 of admission. CT scan was performed in all patients. NLRwas calculated using these data.Every patient was followed regularly for identification of organ failure. Statistical analysis was done with SPSS V22. Results: Among 117 patients, 67(57.3%) were male and 50(42.73%) were female with a mean age of 47.99±15. Among the patients the etiology was found to be biliary, hypertriglyceridemia, alcohol, malignancy and post-ERCP complications in 25(21.4%),23(19.7%),8(6.8%),3(2.6%),2(1.7%) cases respectively. In 53(45.3%) cases no definite etiology could be found. 83(70.9%) patients had mild,15(12.8%) had moderately severe and 19(16.2%) had severe acute pancreatitis. 23 (19.65%) patients developed complication, whereas 94 (80.34%) developed no complication.Organ failure was present in 34(29.06%) cases among total 117 cases.Those patients who developed organ failure had a mean NLR of 6.25±0.96, in contrast to a mean of 3.64±0.50 in those who didn’t developed organ failure.ROC curve evaluating the role of NLR in predicting development of organ failure in acute pancreatitis showed an AUC of 0.984. ROC curve revealed a cutoff point of 5.04 with highest sensitivity (97.1%) & specificity (97.6%) with a PPV & NPV of 94.3% & 98.8% respectively. Conclusion: Calculating NLR is simple, it is readily available, easy to assess and cost-effective. It can be used as a new simple & cost-effective marker for the prediction of development of organ failure in Acute Pancreatitis. Mediscope Vol. 8, No. 1: January 2021, Page 45-52